2005
DOI: 10.2193/0022-541x(2005)069[1053:pcictm]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Pellet Count Indices Compared to Mark–recapture Estimates for Evaluating Snowshoe Hare Density

Abstract: Snowshoe hares (Lepus americanus) undergo remarkable cycles and are the primary prey base of Canada lynx (Lynx canadensis), a carnivore recently listed as threatened in the contiguous United States. Efforts to evaluate hare densities using pellets have traditionally been based on regression equations developed in the Yukon, Canada. In western Montana, we evaluated whether or not local regression equations performed better than the most recent Yukon equation and assessed whether there was concordance between pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 29 publications
3
75
1
Order By: Relevance
“…The area is temperate boreal coniferous forest comprising an array of uncut and harvested stands mostly on US Forest Service lands that are largely unpopulated. Hare densities in this region vary but tend to be less than two hares per ha (34). Snowshoe hares were livetrapped using Tomahawk traps (Tomahawk Live Trap Company, Tomahawk, WI) and fitted with radiocollars (Wildlife Materials, Murphysboro, IL) (17).…”
Section: Methodsmentioning
confidence: 99%
“…The area is temperate boreal coniferous forest comprising an array of uncut and harvested stands mostly on US Forest Service lands that are largely unpopulated. Hare densities in this region vary but tend to be less than two hares per ha (34). Snowshoe hares were livetrapped using Tomahawk traps (Tomahawk Live Trap Company, Tomahawk, WI) and fitted with radiocollars (Wildlife Materials, Murphysboro, IL) (17).…”
Section: Methodsmentioning
confidence: 99%
“…Our model is the first to provide a quantitative match to cycle probes that include peak and low densities. Although low densities can be difficult to estimate accurately from field data (Mills et al 2005), all of the snowshoe hare density estimates were based on reliable mark-recapture live-trapping (Boulanger and Krebs 1996), thus providing high-quality information about this important phase of the cycle. Our model is the first to capture the very low minimum hare densities observed in the boreal forest near Kluane Lake (Hodges et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…For rectangular plots, counts of uncleared plots were on average 1.1-fold higher than cleared plots, whereas for circles uncleared plots were 1.7-fold higher. Both cleared and uncleared plots were highly correlated with snowshoe hare density estimates from mark-recapture data (Mills et al, 2005;Hodges and Mills, unpublished data). People were not consistent at aging pellets of unknown age as >1-year-old or <1-year-old.…”
Section: Field Datamentioning
confidence: 97%
“…Mills et al (2005) found that pellet densities of 0.6 and 1.6 per small rectangular plot in western Montana were useful thresholds, as pellet densities <0.6 signified hare densities <0.3 hares/ha, while pellet densities of >1.6 indicated hare densities >0.7 hares/ha; in between, the relationship between hare density and pellet density was too variable for reliable inference about hare density.…”
Section: Simulationsmentioning
confidence: 99%
See 1 more Smart Citation